2019
DOI: 10.3389/fmicb.2019.01934
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of the Immune Response by Human Pathogenic Mycoplasmas

Abstract: Mycoplasmas are a large group of prokaryotes which is believed to be originated from Gram-positive bacteria via degenerative evolution, and mainly capable of causing a wide range of human and animal infections. Although innate immunity and adaptive immunity play crucial roles in preventing mycoplasma infection, immune response that develops after infection fails to completely eliminate this bacterium under certain circumstances. Thus, it is reasonable to speculate that mycoplasmas employ some mechanisms to dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 110 publications
0
24
0
1
Order By: Relevance
“…Because M. pneumoniae has no cell wall, its cell membrane is the major structure that interacts with the host [3]. Previous studies have shown that membrane lipoproteins (or lipidassociated membrane proteins) of M. pneumoniae are important proinflammatory molecules [6,7]. Classical membrane lipoproteins contain an N-terminal diacylglycerol cysteine structure, and this particular lipid moiety is the basis for the proinflammatory activity following an M. pneumoniae infection [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because M. pneumoniae has no cell wall, its cell membrane is the major structure that interacts with the host [3]. Previous studies have shown that membrane lipoproteins (or lipidassociated membrane proteins) of M. pneumoniae are important proinflammatory molecules [6,7]. Classical membrane lipoproteins contain an N-terminal diacylglycerol cysteine structure, and this particular lipid moiety is the basis for the proinflammatory activity following an M. pneumoniae infection [8].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that in spite of the limited inflammatory response triggered by CV2 cells (Fig 2 ), our results indicate that repeated injections of CV2 cells generate an IgG response (Fig EV4 ), which could potentially affect the efficacy of long‐term treatments or those involving repeated use. However, this IgG response might not necessarily limit the efficacy of CV2‐based treatments in a subcutaneous setting, as mycoplasma‐associated infections are characterized by the subversion of host immune responses (Qin et al , 2019 ). In any case, this is an interesting result, as so far most of the bacterial therapies available are targeted to the gastrointestinal tract, an environment in which the immune system has evolved to establish tolerance toward an enormous and constantly changing amount of microorganisms (Zheng et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of eDNA in the biology of M. bovis is consistent with functional genomic studies with several ruminant mycoplasma species that identified nucleotide metabolism as essential for their survival in cell culture, while dispensable for axenic growth (Baranowski et al, 2010; Skapski et al, 2011; Josi et al, 2019). Finally, nucleases and polynucleotide binding proteins are common component of the mycoplasma surface, besides their role in the acquisition of nutrients these surface proteins are also emerging as potential virulence factors (Minion and Goguen, 1986; Minion et al, 1993; Bendjennat et al, 1999; Jarvill-Taylor et al, 1999; Schmidt et al, 2007; Li et al, 2010, 2018, 2019a; Somarajan et al, 2010; Szczepanek et al, 2010; Browning et al, 2011; Cacciotto et al, 2013, 2019; Masukagami et al, 2013; Sharma et al, 2015; Xu et al, 2015; Yacoub and Mardassi, 2016; Zhang et al, 2016; Gondaira et al, 2017; Yamamoto et al, 2017; Mitiku et al, 2018; Qin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%